2023
DOI: 10.11591/ijece.v13i2.pp1570-1579
|View full text |Cite
|
Sign up to set email alerts
|

Flexible handover solution for vehicular ad-hoc networks based on software defined networking and fog computing

Abstract: <p>Vehicular ad-hoc networks (VANET) suffer from dynamic network environment and topological instability that caused by high mobility feature and varying vehicles density. Emerging 5G mobile technologies offer new opportunities to design improved VANET architecture for future intelligent transportation system. However, current software defined networking (SDN) based handover schemes face poor handover performance in VANET environment with notable issues in connection establishment and ongoing communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, these works are based on the traditional network that does not have enough flexibility to control the network. To overcome this issue, we are witnessing research works applying Software-Defined Networking (SDN) as their network solution for MEC [9]- [14].…”
Section: Related Workmentioning
confidence: 99%
“…However, these works are based on the traditional network that does not have enough flexibility to control the network. To overcome this issue, we are witnessing research works applying Software-Defined Networking (SDN) as their network solution for MEC [9]- [14].…”
Section: Related Workmentioning
confidence: 99%
“…Mouad et al [24], proposed a big data-based technique to balance different roads of the city by directing vehicles to their destination relying on the estimated time of arrival. The research paper identified as [25], introduces a method that proposes a flexible transfer especially for VANET by including fog computing and software defined networking (SDN) technologies. The experiment evaluation proves a good transfer performance amelioration of the proposed solution.…”
mentioning
confidence: 99%